TRAINING AND ASSISTANCE ON DIGITALIZATION OF TEACHING MATERIALS FOR TEACHERS FOR ONLINE LEARNING AT 3T SCHOOLS AT SMAN 1 MUARA TIGA REGENCY. PIDIE - Rahmad Junaidi; Riyan Maulana; Ulfa Irani Z (Jurnal Pengabdian Bangsa, 2022)
The problem underlying this community service is the limited skills of teachers at SMA 1 Muara Tiga District. Pidie organizes the online learning process using online features. The aim of this service is to provide understanding and skills in utilizing online features as an online learning medium. The training method is carried out by lectures, discussions and exercises. The results of this service activity are; Teachers understand the features used in implementing online learning, have skills in using online features such as Zoom Meeting and Google Classroom. Another benefit obtained from this training is that apart from being able to learn online, participants are also equipped with the skills to make learning videos using the zoom meeting feature by presenting the material accompanied by a display of the learning material. This is one strategy for implementing offline-based learning, so that students do not depend on the internet network.